Alkali Activated Binders Based on Metakaolin (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
According to research conducted in last 25 years, alkali activated binders have been considered as one of the most progressive alternative binders, which can effectively replace Portland cement. Production of alkali activated binders differs from the Portland cement production and is associated with lower CO2 emissions. The use of recycled industrial by-products and wastes is also possible, what corresponds to the future guidelines and principles of sustainable binder production in the world.The aim of this study was to create innovative alkali activated binders by using secondary raw materials, which will be different from the ones described in the scientific literature – alkali activated binders with porous structure. Raw materials used for the binders were metakaolin containing waste, waste from aluminium scrap recycling factory and recycled lead-silicate glass; solid contents were activated with modified sodium silicate solution with an addition of sodium hydroxide.The physical properties of alkali activated binders, such as density, water absorption, open and total porosity, were determined and flexural and compressive strength of hardened alkali-activated binders were tested at the age of 28 days. Durability was examined by sulphate resistance test, which was performed according to SIA 262/1, appendix D: applicability and relevance for use in practice. 40x40x160 mm prismatic specimens were used for expansion measurement and determination of compressive strength. The open porosity of obtained materials was up to 45%, density from 380 to 1720 kg/m3, compressive strength up to 29,8 MPa, water absorption 6 – 114 wt.%. After analysing the results from the sulphate test it was concluded that glass additive reduced the alkali activated binder resistance to sulphate attack.